Application of a microwave synthesized ultra-smooth a-C thin film for the reduction of dielectric/semiconductor interface trap states of an oxide thin film transistor. Issue 40 (23rd September 2022) - Pal, Nila; Thakurta, Baishali; Chakraborty, Rajarshi; Pandey, Utkarsh; Acharya, Vishwas; Biring, Sajal; Pal, Monalisa; Pal, Bhola N.
Abstract : Improvement in TFT performance has been achieved by introducing a solution-processed ultra-smooth nitrogen-doped amorphous carbon (a-C) thin film in between gate dielectric and semiconductor. Abstract : In high- κ dielectric-based thin-film transistors (TFTs), tailoring the surface of the gate dielectric layer is a crucial issue for the improvement of the device performance. Herein, a simple solution-processed ultra-smooth amorphous-carbon (a-C) film is applied as a surface modification layer on the top of the high- κ ion-conducting Li–Al2 O3 dielectric of a bottom gated SnO2 TFT. The a-C film minimizes the surface roughness of the gate dielectric and forms a strong coordination bond between the doped nitrogen of the a-C film and tin (Sn) of the upper lying SnO2 semiconducting channel, which lowers the gate leakage current, carrier scattering and trap state density at the dielectric/semiconductor interface successfully. As a consequence, the TFT with an a-C interface shows an improvement in the carrier mobility by 6.7 times with a higher ON/OFF ratio and a lower subthreshold swing (SS) by 3.8 times. An optimized device with an a-C gate interface shows a saturation carrier mobility, ON/OFF ratio and SS value of 21.1 cm 2 V −1 s −1, 7.0 × 10 4, and 147 mV dec −1, respectively. Moreover, a significant improvement in the cycling electrical stability has been observed which is an outcome of a reduced trap state of an a-C modified TFT.